2012
DOI: 10.1590/s1809-29502012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da lordose lombar e sua relação com a dor lombopélvica em gestantes

Abstract: | The purpose of this study was to evaluate the magnitude of lumbar lordosis, its influence on lumbopelvic pain and quality of life in pregnant women. To this end, a study was done with 20 non-pregnant women (C) and 13 pregnant women during the trimesters of pregnancy (G1, G2 and G3). All women underwent initial assessment for registration of personal data, lifestyle, personal history, medications, gynecological and obstetric history. Later, the volunteers in the control group were evaluated once and pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
0
0
6
Order By: Relevance
“…Concerning reproductive history, it was observed that the higher the number of births, the chance of presenting CBP increases by 37%. This association has also been found in other studies that consider pregnancy and postpartum as explanatory factors for higher prevalence of back pain among women 25,41,42 . This can be explained by pregnancy hormones such as relaxin, estrogen, and progesterone, which are responsible for increasing flexibility of the spinal and hip ligaments and lumbar lordosis increase, increased muscle contractions due to increased weight and posture caused by fetal growth.…”
Section: Discussionsupporting
confidence: 85%
“…Concerning reproductive history, it was observed that the higher the number of births, the chance of presenting CBP increases by 37%. This association has also been found in other studies that consider pregnancy and postpartum as explanatory factors for higher prevalence of back pain among women 25,41,42 . This can be explained by pregnancy hormones such as relaxin, estrogen, and progesterone, which are responsible for increasing flexibility of the spinal and hip ligaments and lumbar lordosis increase, increased muscle contractions due to increased weight and posture caused by fetal growth.…”
Section: Discussionsupporting
confidence: 85%
“…No que diz respeito ao histórico reprodutivo, observou-se que quanto maior o número de partos, a chance de apresentar PCC aumenta em 37%. Essa associação também já foi encontrada em outros estudos que consideram a gravidez e o pós-parto como fatores explicativos de maior prevalência de dores na coluna entre mulheres 25,41,42 . Isso pode ser explicado pelos hormônios da gravidez, como a relaxina, estrógeno e progesterona, que são responsáveis por aumentar a flexibilidade dos ligamentos da coluna e quadril e aumento da lordose lombar, aumento das contraturas musculares devido ao aumento do peso e à postura causados pelo crescimento do feto.…”
Section: Discussionunclassified
“…Firmento [19] avaliou 13 gestantes buscando detectar possíveis estratégias utilizadas pelo corpo a fim de compensar o aumento localizado de peso, no entanto neste estudo não foi observada a relação entre a curvatura lombar e a dor pélvica. O estudo de Mann [20] aponta que os prováveis motivos para lombalgia nesse período são decorrentes da ação do hormônio relaxina que provoca mudanças na mobilidade articular e ligamentar podendo aumentar a curvatura lombar e torácica de gestantes entre o 4 o e o 9 o mês.…”
Section: Discussionunclassified